Acculturation, Internet Use, and Psychological Well-being Among Chinese International Students - Li, Jia Qi; Liu, Xun; Wei, Tianlan; Lan, William (Journal of International Students, 2013)
In this study, the authors examined the relationships of acculturation as measured with two subscales of cultural maintenance and cultural assimilation, Internet use, and psychological wellbeing among Chinese international students. A total of 170 Chinese international students participated in this study. Bivariate correlation analyses revealed that an individual can identify with two different cultures, minority and dominant culture. Results of multiple regression indicated that cultural assimilation was a significant predictor to psychological well-being, but not cultural maintenance. The study also found that younger Chinese international students (e.g., students pursuing bachelor’s degrees) suffered significantly higher levels of stress and depression in the acculturation process as compared to their older counterparts. Implications for counseling and recommendations for future research were discussed.